2020
DOI: 10.22146/ijcn.53788
|View full text |Cite
|
Sign up to set email alerts
|

Early introduction of complementary food and childhood stunting were linked among children aged 6-23 months

Abstract: Background: Indonesia’s national stunting prevalence remains high. The transition from exclusive breastfeeding to poor complementary feeding practices may put infants at higher risk of becoming stunting. Objective: This study aimed to analyze the relationship between the early introduction of complementary food and stunting among young children aged 6-23 months in Kebumen Regency. Methods: A cross-sectional study design was conducted among 307 young children in Kebumen Regency, Central Java Province, Indonesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
12
0
7
Order By: Relevance
“…A recent cross-sectional study from Indonesia also found similar results to this finding and portrays that untimely introduction of complementary food was associated with stunting in children. Children who obtain their first food before six months of age are two times more likely to become stunted than their counterparts [ 38 ]. Likewise, a more recent study from Ethiopia also strengthened the idea that early initiation of complementary feeding before six months of age significantly (AOR = 1.58: 95%, CI, 1.07, 2.34) contributed to stunting in children [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study from Indonesia also found similar results to this finding and portrays that untimely introduction of complementary food was associated with stunting in children. Children who obtain their first food before six months of age are two times more likely to become stunted than their counterparts [ 38 ]. Likewise, a more recent study from Ethiopia also strengthened the idea that early initiation of complementary feeding before six months of age significantly (AOR = 1.58: 95%, CI, 1.07, 2.34) contributed to stunting in children [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic energy deficiency is a state caused by an imbalance between consumption and needs (energy and protein). occurs due to lower energy consumption than the amount of energy needed by the body, which lasts for many years Chronic energy deficiency can be known from the value of the upper arm circumference limit which is ≤ 23.5 cm (Amalia et al 2018;Mutaghfiroh et al 2019;Paramashanti, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely A recent cross-sectional study from Indonesia also found similar result with this nding and portrays that untimely introduction of complementary food associated with stunting of children. Children those get their rst food before six months of age are two times more likely become stunted as compared to their counterparts [27]. Likewise, more recent study from Ethiopia also strengthened the idea that early initiation of complementary feeding before six months of age signi cantly (AOR = 1.58; 95%, CI, 1.07, 2.34) attributed for stunting of children [28].…”
Section: Discussionmentioning
confidence: 96%